Activity, Abundance, and Localization of Quorum Sensing Receptors in Vibrio harveyi - Lorenz, Nicola; Shin, Jae Yen; Jung, Kirsten (Frontiers in Microbiology, 2017)
Quorum sensing (QS) is a process enabling a bacterial population to communicate via small molecules called autoinducers (AIs). This intercellular communication process allows single cells to synchronize their behavior within a population. The marine bacterium Vibrio harveyi ATCC BAA-1116 channels the information of three AI signals into one QS cascade. Three receptors perceive these AIs, the hybrid histidine kinases LuxN, Lux(P)Q and CqsS, to transduce the information to the histidine phosphotransfer (HPt) protein LuxU via phosphorelay, and finally to the response regulator LuxO. Hence, the level of phosphorylated LuxO depends on the AI concentrations. The phosphorylated LuxO (P-LuxO) controls the expression of small regulatory RNAs (sRNAs), which together with the RNA chaperon Hfq, destabilize the transcript of the master regulator luxR. LuxR is responsible for the induction and repression of several genes (e.g. for bioluminescence, exoprotease and siderophore production). In vivo studies with various mutants have demonstrated that the ratio between kinase and phosphatase activities of the individual QS receptors and therefore the P-LuxO/LuxO ratio is crucial not only for the output strength but also for the degree of noise. This study was undertaken to better understand the inherent design principles of this complex signaling cascade, which allows sensing and integration of different signals, but also the differentiated output in individual cells. Therefore, we quantitatively analyzed not only the enzymatic activities, but also the abundance and localization of the three QS receptors. We found that LuxN presents the highest capacity to phosphorylate LuxU, while the phosphatase activity was comparable to LuxQ and CqsS in vitro. In whole cells the copy number of LuxN was higher than that of LuxQ and CqsS, and further increased in the late exponential growth phase. Microscopy experiments indicate that LuxN and LuxQ form independent clusters. Altogether, these results suggest, that the three QS receptors act in parallel, and V. harveyi has developed with LuxN the most dynamic sensing range for HAI-1, the species-specific AI.